Contiguity of Law Violations in the Context of Business Competition and Corruption in Bid Rigging Cases - Tobing, Martuasah Hermindo; Sirait, Ningrum Natasya; Siregar, Mahmul (Journal of Ecohumanism, 2024)
Contiguity can be found in law violations regarding business competition and corruption in bid rigging cases. The purpose of this study was to determine the intersection of unlawful acts in the context of tender conspiracy and corruption. It is assumed that all corruption cases stem from bid rigging, both horizontally and vertically. Bid rigging is considered a violation of Article 22 of Law Number of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (Anti-Monopoly Law) but is later considered an act of corruption based on Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption (Anti-Corruption Law). The method used in handling these cases is determined by the Business Competition Supervisory Commission (BCSC). The results showed that in making decisions regarding bid rigging, the BCSC used an interpretation method derived from doctrines. From a law enforcement perspective, there are overlapping laws and regulations. For this reason, a joint investigation is needed between the BCSC and other law enforcement institutions (the Corruption Eradication Commission, the Attorney General’s Office, and the Police) to determine whether or not any laws are violated in the context of business competition and corruption in cases of bid rigging.